Legal Reforms on Femicide in Indonesia: The New Criminal Code, Victim Protection, and the Role of Islamic Law - Antory Royan Adyan; Ariesta Wibisono Anditya (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
Femicide, the killing of women based on their gender, is a grave issue with widespread societal implications. This phenomenon reflects the high level of gender-based violence and demands urgent attention from all sectors, including the government, legal institutions, and society at large. This study aims to examine femicide within the context of national law, victimology, and Islamic law, with a focus on the protection and justice for victims in Indonesia. This research utilizes normative legal methods by adopting statutory, conceptual and comparative approaches. The nature of this research is descriptive-prescriptive. The collected data is analyzed using content analysis method. The findings of this research indicate that Law No. 1 of 2023 on the Criminal Code regulates various forms of murder, including premeditated murder and serious maltreatment, with different sanctions. The articles in this law, while not specifically mentioning femicide, provide an important legal framework for prosecuting perpetrators of violence against women that leads to death. Despite not explicitly using the term “femicide,” these provisions establish a protective framework for women against extreme violence. Learning from countries such as Mexico, Spain, India which have clear femicide laws, can strengthen the legal framework in Indonesia, and integrating Islamic principles, such as the sanctity of life emphasized in Surah Al-Ma’idah verse 32, Surah An-Nisa verse 93, Surah Al-Isra verse 33, Surah An-Nisa verse 1, Surah Al-Baqarah verse 195, and Surah Al-Mumtahanah verse 8, with modern laws can further strengthen efforts to combat femicide. A holistic approach, including prevention, protection, and healing for victims, is essential to creating a safer environment for women and ensuring justice.